Third opinion leadership for quality of financial decision making / Rikinorhakis Ridzwan - Ridzwan, Rikinorhakis (2013)
Third opinion is a leadership style that was adopted from Joni (2004) which relies on outsider’s opinion in influencing their decision-making process. There are three characteristics of third opinion proposed in this study, which are third opinion’s mind that is people with knowledge and high thinking level; third opinion’s relationship that is people based on personal trust and networking; and third opinion’s focus that is people who have idea, creativity and innovativeness. This research advocates that third opinion is contingent upon the relationship between leadership behavioral style initiated from Path-goal theory by House and Mitchell (1974) and Situational theory by Hersey and Blanchard (1977). Leadership style therefore is conceptualized based on four dimensions namely directive behavioral style, supportive behavioral style, participative behavioral style and achievement-oriented behavioral style. 211 data were collected from managers in different sectors through questionnaires survey. All results were obtained from SPSS (19.0) using four major statistical techniques which are factor analysis, reliability analysis, descriptive analysis and regression analysis.The findings indicate that third opinion for financial decision making is moderately important for Malaysian managers and has significant difference among leadership style. Regression analysis shows that the quality of financial decision is significant and positively related to leadership style. Third opinion’s mind and third opinion’s relationship act as pure moderator, while third opinion’s focus was found to be a quasi-moderator. For theoretical implication, the findings suggest that the inclusion of the moderating variable will further enhance the understanding of the differential impact of leadership style under various contexts of decision-making situation, in this case, the third opinion. For future research, it is recommended that differences relation to leadership styles should be studied more extensively to reach various kinds of comparative conclusions.